Konservatisme Akuntansi Dan Faktor-Faktor Yang Mempengaruhinya - Utami Puji Lestari; Devi Dwi Kurniawan; Ahmad Dwi Nurdiyanto (Jurnal Ekonomika dan Bisnis, 2022)
Utami Puji Lestari. Accounting conservatism and the factors that influence it.Semarang institute of technology and business.10 pages.The number of samples to peneilitian 78 of several manufacturing companies this the the food and drink that are only sampled this research as many as 26 company with a period of observation for 3 years.With the sample collection use purposive the sampling method of.The research results show that financial distress has not been affecting the accounting conservatism.Leverage has not been affecting the accounting conservatism, the size of the company to depend on the accounting conservatism.